Mathematical modelling and simulation for biogas production from organic waste. (2018) - Delgadillo-Mirquez, Liliana; Hernández-Sarabia, Mauricio; Machado-Higuera, Maximiliano
This paper introduces the modelling, simulation of anaerobic digestion process for biogas production from organic waste. Insight on the relevant model parameters is obtained by performing a sensitivity analysis, followed by the estimation of the selected candidates using a sequential quadratic programming algorithm. Calibration and validation of the model are based on experimental data obtained from a pilot-scaled plant, showing that the proposed model is able to correctly predict the Methane production dynamics from few key measurements.